2017
DOI: 10.2172/1343542
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Sorption and Diffusion Mechanisms, and Preliminary Economic Analysis

Abstract: This report describes the synthesis and evaluation of molecular sieve zeolite membranes to separate and concentrate tritiated water (HTO) from dilute HTO-bearing aqueous streams. Several monovalent and divalent cation exchanged silico alumino phosphate (SAPO-34) molecular sieve zeolite membranes were synthesized on disk supports and characterized with gas and vapor permeation measurements. The pervaporation process performance was evaluated for the separation and concentration of tritiated water.Experiments we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…The X-Ray Diffraction (XRD) analysis and permeation measurement results showed that high quality membranes were synthesized which are well suited to evaluate the tritiated water vapor sorption and diffusion through the zeolite pores. 15 The characteristic peaks associated with LTA structure are detected in the XRD pattern and it is confirmed that no other competing phases are formed during synthesis. The bulk compositions of the as-synthesized NaA and cation-exchanged KA membranes were determined using EDX analysis of the Na, K, Si and Al content.…”
Section: Characterization Of Ion-exchanged Sapo and Lta Membranesmentioning
confidence: 56%
See 4 more Smart Citations
“…The X-Ray Diffraction (XRD) analysis and permeation measurement results showed that high quality membranes were synthesized which are well suited to evaluate the tritiated water vapor sorption and diffusion through the zeolite pores. 15 The characteristic peaks associated with LTA structure are detected in the XRD pattern and it is confirmed that no other competing phases are formed during synthesis. The bulk compositions of the as-synthesized NaA and cation-exchanged KA membranes were determined using EDX analysis of the Na, K, Si and Al content.…”
Section: Characterization Of Ion-exchanged Sapo and Lta Membranesmentioning
confidence: 56%
“…The rationale for the synthesis and evaluation of cation exchanged SAPO-34 is described by Bhave et al 15 Table 2 shows the results of pervaporation experiments with monovalent (K + , Li + , Na + ) cation exchanged SAPO-34 zeolite membranes. The separation factor (HTO/H 2 O) for the tritiated water separation with neutral SAPO-34 zeolite membrane was 0.83 which indicates that HTO did not preferentially permeate through zeolite pores over H 2 O.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations